Measuring the effectiveness of knowledge management practice at Philip Morris (Malaysia) Sdn. Bhd. / Raja Suzana Raja Kasim - Raja Kasim, Raja Suzana (2002)
Many organizations are seeking means to improve the process of operations and business to increase their performance. Today, managing knowledge is considered one of. the main challenges in modern organizations. In this paper, a case study to explore the employees' perceptions towards the effectiveness of knowledge management practice is conducted. It draws finding of employees' interpretations and applications of knowledge management processes and practice in a variety of organizational contexts. The objectives of this paper lies on identifying solutions to improve such practice of knowledge with a focal points on the leadership support and enhancing knowledge sharing and knowledge access. Based on the assumption that leadership support and knowledge sharing matters to the effectiveness of KM practice, a framework is developed where collaborations and partnership between organizations, technologies and processes can be done. Results are reported from the survey of 43 employees of Philip Morris (Malaysia) Sdn. Bhd. comprise of managers, executives, supervisors and lower level staff. The analysis reveals that although knowledge management is implemented, there are still number of lacking actions in managing the issues of knowledge contents and practice. The obstacles in many of the knowledge content issues with particular concern on the leadership practice, knowledge sharing and its ac'tessibility led to the ineffectiveness process of implementing it successfully. It concludes that the importance of managerial values such as leadership, the culture of knowledge sharing and how knowledge could improve employee tasks have been overlooked in the implementation of knowledge management practice. Consequently, this paper proposes few actions and implementation programs to be done.